PENGARUH GOOD CORPORATE GOVERNANCE DAN AUDITOR EKSTERNAL TERHADAP AUDIT DELAY (STUDI EMPIRIS PADA PERUSAHAAN INDUSTRI PERBANKAN DI BURSA EFEK INDONESIA 2011-2013) - Oktrivina DS , Amelia; Nelyumna (SEKOLAH PASCASARJANA PRESS, 2016)
Audit delay the completion of the audit that the length of time is measured from the date of closing of the financial year until the issuance of the audit report signed by the auditor . Benefits of the financial statements will be reduced if the report is not available on time . This study examines the factors that affect audit delay including the audit committee , board of commissioners , and the external auditors . This study sampled banking companies in Indonesia Stock Exchange , with a sample of 90 for 3 years. This study was measured by using a multiple linear regression model . These results indicate that simultaneous audit committee , board of commissioners , and external auditors have a significant effect on audit delay . Partially , the audit committee , board of commissioners , and the external auditors have a significant effect on audit delay in banking companies in Indonesia Stock Exchange .